Efecto covid-19 en Ecuador: analisis de la recaudacion del impuesto a la renta 2019-2020. - Cabrera Pucha, Dayana Micaela; Paez Abad, Kevin Eduardo (My University, 2021)
This research aims to carry out a comparative analysis of the effects of Covid-19 in the collection of Income Tax in 2020, taking as a reference the collections of 2019. The applied methodology is quantitative-analytical in nature based on collection of statistical data of the Internal Revenue Service of Ecuador and bibliographic review focused on scientific articles, where each of the income tax taxes, withholdings at source, personal and legal income tax, income tax is analyzed. to inheritances, bequests and donations. The results show that the impact generated by the covid19 on the Ecuadorian economy was negative during the months of April to December of the year 2020; The Ecuadorian State as an adjustment measure establishes the deferral of income tax payments, this meant a decrease in income in the tax administration of almost 34% compared to 2019, however, with the recovery of tax collection Only as of September 2020, a significant improvement in income is already perceived.
Esta investigación tiene como objetivo realizar un análisis comparativo de las afectaciones de Covid-19 en la recaudación de Impuesto a la Renta en el año 2020, tomando como referencia las recaudaciones del año 2019. La metodología aplicada es de carácter cuantitativo-analítico basado en recolección de datos estadísticos del Servicio de Rentas Internas del Ecuador y revisión bibliográfica enfocada en artículos científicos, donde se analiza cada uno de los tributos de Impuesto a la Renta, Retenciones en la Fuente, Impuesto a la Renta en Personas y Jurídicas, Impuesto a la Renta a Herencias, Legados y Donaciones. Los resultados demuestran que el impacto generado por el Covid-19 a la economía ecuatoriano fue negativo durante los meses de abril a diciembre del año 2020; el Estado ecuatoriano como medida de ajuste establece el diferimiento de pagos del Impuesto a la Renta, esto significó una disminución de ingresos en la administración tributaria de casi un 34% en comparación con el año 2019, no obstante, con la recuperación de la recaudación tributaria sólo a partir del mes de septiembre del 2020, ya se percibe una mejora significativa en los ingresos.
Keywords: INCOME TAX; COVID-19